Impacto De La Realidad Aumentada En La Educación Del Siglo XXI - Franklin Montecé-Mosquera; Alexis Verdesoto-Arguello; Carlos Montecé-Mosquera; Cesar Caicedo-Camposano (European Scientific Journal, ESJ, 2017)
The vertiginous advances in terms of information anda communication technologies mean allow innovative ways to stregthen aspects related to knowledge. With the passing of the last years the Augmented Reality RA has positioned itself as a technology that has approached different environments of society, environments related to advertising, marketing, video games and in education has generated a high impact. Augmented reality is technology that contributes resources to the world, it seeks to determine if the incorporation of technologies contribute an enrichment to the teaching-learning process. Considering the analysis of works related to the theme, the reality may be d efined as that additional information obtained by observation of an environment with the objective to innovate the teaching process by providing a tool that presents the user: interaction, entertainment and motivation learning.